Peran dan Pengaruh Pendidikan Islam pada Perjuangan Kemerdekaan Indonesia Serta Tokoh-Tokohnya - M.Rasyid; Kasful Anwar US; Sya'roni Sya'roni (Jurnal Budi Pekerti Agama Islam, 2024)
This research discusses the role and influence of Islamic education in the struggle for Indonesian independence and its figures. With the objectives, among others, to analyze the role of Islamic education, especially Islamic boarding schools and religious organizations, in building awareness of nationalism and the spirit of independence in the younger generation, as well as in preparing them to face the colonizers, and evaluating the impact of the moral and spiritual values taught in Islamic education on the formation of the character of the freedom fighters, as well as how these values affect their spirit and courage in resisting the colonizers.Islamic education plays a central role in the long journey towards Indonesian independence. In the midst of resistance to the invaders, Islam not only gave spiritual strength to the fighters, but also became the moral and intellectual foundation that guided their steps. Since the beginning of the 20th century, Islamic educational institutions such as Islamic boarding schools have become centers of learning and spreading the spirit of struggle against colonial oppression. Scholars and religious leaders, such as KH Ahmad Dahlan, the founder of Muhammadiyah, actively played an important role in mobilizing the masses and spreading nationalist ideas rooted in Islamic values. Figures such as KH Hasyim Asy'ari from Nahdlatul Ulama (NU) also had a big impact on the struggle. Through Islamic boarding schools and religious organizations, NU built a strong network of solidarity among the Muslim community, rallying support for the struggle for independence. In addition, women's active participation in Islamic education, especially through organizations such as Aisyiyah, makes a significant contribution to fighting for rights and freedoms for all Indonesian people. Thus, Islamic education not only provides the foundation for Indonesia's independence, but also prepares the younger generation as resilient and responsible agents of change.